Exploring skin picking disorder: aetiology, treatment, and future directions - Alfahaad, Hamad; Aldehri, Majed; Alsaiari, Soliman Ayed; Asiri, Fayeh; Alfataih, Mahdi; Alahmari, Saeed (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2024)
Skin picking disorder (SPD) is a psychiatric condition characterized by repetitive picking of the skin, causing damage to tissue and significant distress. Despite its prevalence and impact, SPD remains understudied and often overlooked in clinical practice. This review thoroughly examines SPD, including its epidemiology, aetiology, clinical presentation, methods of treatment, challenges, and future directions. The review highlights the multifactorial nature of SPD, involving genetic, neurobiological, and psychological factors. Clinical presentation of SPD includes compulsive skin picking behaviours, emotional distress, and impaired social functioning. This review underscores the importance of recognizing and addressing SPD, emphasizing the need for integrated approaches to assessment, treatment, and research. By advancing our understanding of SPD, we can improve outcomes and quality of life for individuals affected by this disorder.